2019
DOI: 10.12968/bjon.2019.28.2.s4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience of a subcutaneously anchored sutureless system for securing central venous catheters

Abstract: This article reports the results of three prospective clinical studies conducted in a university hospital regarding the efficacy, safety and cost effectiveness of a subcutaneously anchored sutureless system for securing central venous catheters. The results were favourable to the adoption of such a device, and the analysis of the data allowed the authors to define those categories of patients where the device should have the most benefit: neonates, children, non-compliant older patients with cognitive difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 9 publications
0
35
0
Order By: Relevance
“…As reported by these three cases, we are currently testing an innovative approach to chest tube securement, using a new subcutaneously anchored sutureless device (SAS) (SecurAcath, Interrad) initially marketed for the securement of central venous catheters. Its safety, efficacy, and cost effectiveness are well acknowledged in the world of vascular access [2][3][4][5]. SAS has also been used for other purposes: for instance, as securement of cerebral-spinal catheters [6], biliary tube drainage, and nephrostomy tubes [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported by these three cases, we are currently testing an innovative approach to chest tube securement, using a new subcutaneously anchored sutureless device (SAS) (SecurAcath, Interrad) initially marketed for the securement of central venous catheters. Its safety, efficacy, and cost effectiveness are well acknowledged in the world of vascular access [2][3][4][5]. SAS has also been used for other purposes: for instance, as securement of cerebral-spinal catheters [6], biliary tube drainage, and nephrostomy tubes [7].…”
Section: Discussionmentioning
confidence: 99%
“…Also, we noticed that insertion of SAS by anchoring it in the subcutaneous tissue was extremely easy. As suggested by our previous experience with SAS for securement of central venous catheters in neonates, we placed a small piece of sterile gauze under the base of the device so to avoid the risk of an excessive pressure of the device over the delicate skin [2].…”
Section: Discussionmentioning
confidence: 99%
“…This review demonstrated savings in clinician time, material costs, and the benefits of reduced MARSI-associated tissue injury, highlighting benefits with the use of this securement device. 17 Finally, the most recently published study by Pittiruti et al 18 reported outcomes of three prospective, non-controlled clinical studies evaluating SESD over several years evaluating various venous access devices -PICCs, centrally inserted central catheters (CICCs) and femorally inserted central catheters (FICC). These combined studies reported improved outcomes in several adult high-risk groups, as well as infants and children.…”
Section: Discussionmentioning
confidence: 99%
“…This study confirmed the efficacy, safety and costeffectiveness of SESD when adopted for securement of CVCs, either tunnelled or non-tunnelled, in specific populations of patients: neonates, children, non-compliant older patients, patients with skin abnormalities that may reduce the effectiveness of a skin adhesive sutureless securement, patients who are candidates for maintaining a PICC for more than 8 weeks, and any category of patients with a high risk of catheter dislodgement. 18…”
Section: Discussionmentioning
confidence: 99%
“…The correct tip location was verified during the procedure, by IC-ECG and/or TTE. The catheter was secured by a subcutaneously anchored sutureless device, 11 and the exit site was covered with a semipermeable transparent dressing.…”
Section: Group Bmentioning
confidence: 99%